2010
DOI: 10.1021/ja103235g
|View full text |Cite
|
Sign up to set email alerts
|

Arylethynyl Derivatives of the Dihydroazulene/Vinylheptafulvene Photo/Thermoswitch: Tuning the Switching Event

Abstract: A selection of dihydroazulene (DHA) photoswitches incorporating an arylethynyl-substituent in the seven-membered ring was prepared by palladium-catalyzed Sonogashira cross-coupling reactions employing a suitable bromo-functionalized DHA. Shielding of the alkyne bridge and separating the aryl and DHA units, by sterically demanding groups, was required to obtain stable compounds. The DHAs underwent a light-induced ring-opening to vinylheptafulvenes (VHFs) which were thermally converted to a mixture of two DHA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 49 publications
7
90
0
Order By: Relevance
“…[5, 6,8] Instead the Suzuki cross-coupling was carried out using fluoride to activate the aryl boronic acid. [9] The choice of fluoride source proved to be important; the use of Bu 4 NF was accompanied by substantial azulene formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5, 6,8] Instead the Suzuki cross-coupling was carried out using fluoride to activate the aryl boronic acid. [9] The choice of fluoride source proved to be important; the use of Bu 4 NF was accompanied by substantial azulene formation.…”
Section: Resultsmentioning
confidence: 99%
“…[6] It was found that the electronic properties of the substituent on the phenyl ring (R = NH 2 , H, or NO 2 ) was transmitted through the alkyne bridge. Property tuning is a desirable feature of photochromic systems, and by moving the substituent closer to the seven-membered ring, the influence of the substituent should be more pronounced.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal ring-closure hereof gave a mixture of the original 7-bromo DHA 17 and the 6-bromo DHA 22 (Scheme 9). 33 The two DHA regioisomers can be easily distinguished by 1 H-NMR spectroscopy, and a COSY spectrum supported the assignment of the new DHA isomer as being the C-6 substituted. Regioselective methods for obtaining DHA regioisomers with functional groups at the remaining positions in the seven-membered ring are still unknown.…”
Section: Reactivity and Functionalization Of The Seven-membered Ring mentioning
confidence: 74%
“…[31][32][33][34] It consists of a sequential bromination/elimination protocol, which furnished selectively the 7-bromo DHA 17 starting from DHA 1 (Scheme 7). Addition of up to three molar equivalents of elemental bromine was possible in the first step (Scheme 8).…”
Section: Reactivity and Functionalization Of The Seven-membered Ring mentioning
confidence: 99%
See 1 more Smart Citation